2022
DOI: 10.3390/ijerph19127510
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Defense and Gut Microbial Changes under Pollution Stress in Carassius gibelio from Bucharest Lakes

Abstract: Fish are able to accumulate by ingestion various contaminants of aquatic environment, with negative consequences on their intestine, being continuously threatened worldwide by heavy metals, pesticides and antibiotics resulted from the human activities. Consequently, the health of other species can be affected by eating the contaminated fish meat. In this context, our study aimed to perform a comparison between the changes in intestine samples of Carassius gibelio individuals collected from different artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…WWTPs have been hotspots for increasing the populations of antibiotic-resistant bacteria, especially during the COVID-19 pandemic, triggering a wide range of consequences such as contamination of wastewater treatment plant workers [30]. In addition, their contamination with antibiotic-resistant bacteria could increase the chances of nosocomial diseases generation once these workers or their first contact relatives come in contact with healthcare units.…”
Section: Discussionmentioning
confidence: 99%
“…WWTPs have been hotspots for increasing the populations of antibiotic-resistant bacteria, especially during the COVID-19 pandemic, triggering a wide range of consequences such as contamination of wastewater treatment plant workers [30]. In addition, their contamination with antibiotic-resistant bacteria could increase the chances of nosocomial diseases generation once these workers or their first contact relatives come in contact with healthcare units.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that sediment physicochemical factors and HMs co‐drove microbial variation, but HMs continue to be the main driving factors of fungal communities (Yao et al, 2022). When compared to fish from Bucharest lakes designed for leisure (Chitila, Floreasca and Tei lakes), which experienced increased levels of oxidative stress based on the examination of their intestinal tissues, fish from a protected environment (Vacaresti lake) had a modified antioxidative status due to increased levels of HMs (Fe, Ni and Pb) in their intestines (Alistar et al, 2022). In bighead carp ( Hypophthalmichthys nobilis ), Pb may lead to the destruction of the intestinal barrier, leading to a disordered intestinal microbial community, which in turn promotes the occurrence of cell apoptosis (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In bighead carp ( Hypophthalmichthys nobilis ), Pb may lead to the destruction of the intestinal barrier, leading to a disordered intestinal microbial community, which in turn promotes the occurrence of cell apoptosis (Liu et al, 2020). There are many related studies on the ways that HMs cause harm to fish (Alistar et al, 2022; Liu et al, 2020; Shahjahan et al, 2022). However, the interactions between environmental and intestinal microbiota in cultured fish require further investigation, especially in aquaculture.…”
Section: Introductionmentioning
confidence: 99%